Seasonal and Spatial Variations in Bacterial Communities From Tetrodotoxin-Bearing and Non-tetrodotoxin-Bearing Clams - Biessy, Laura; Pearman, John K.; Smith, Kirsty F.; Hawes, Ian; Wood, Susanna A. (Frontiers in Microbiology, 2020)
Tetrodotoxin (TTX) is one of the most potent naturally occurring compounds and is responsible for many human intoxications worldwide. Paphies australis are endemic clams to New Zealand which contain varying concentrations of TTX. Research suggests that P. australis accumulate the toxin exogenously, but the source remains uncertain. The aim of this study was to identify potential bacterial TTX-producers by exploring differences in bacterial communities in two organs of P. australis: the siphon and digestive gland. Samples from the digestive glands of a non-toxic bivalve Austrovenus stutchburyi that lives amongst toxic P. australis populations were also analyzed. Bacterial communities were characterized using 16S ribosomal RNA gene metabarcoding in P. australis sourced monthly from the Hokianga Harbour, a site known to have TTX-bearing clams, for one year, and from ten sites with varying TTX concentrations around New Zealand, and in A. stutchburyi from the Hokianga Harbour. Tetrodotoxin was detected in P. australis from sites all around New Zealand and in all P. australis collected monthly from the Hokianga Harbour. The toxin averaged 150 µg kg-1 over the year of sampling in the Hokianga Harbour but no TTX was detected in the A. stutchburyi samples from the same site. Bacterial species diversity differed amongst sites (p < 0.001, F = 5.9) and the diversity in siphon samples was significantly higher than in digestive glands (p < 0.001, F = 65.8). Spirochaetaceae (4-60%) and Mycoplasmataceae (16-78%) were the most abundant families in the siphons and the digestive glands respectively. The bacterial communities were compared between sites with the lowest TTX concentrations and the Hokianga Harbour (site with the highest TTX concentrations), and the core bacterial communities from TTX-bearing individuals were analyzed. The results from both spatial and temporal studies corroborate with previous hypotheses that Vibrio and Bacillus could be responsible for the source of TTX in bivalves. The results from this study also indicate that marine cyanobacteria, in particular picocyanobacteria (e.g., Cyanobium, Synechococcus, Pleurocapsa and Prochlorococcus), should be investigated further as potential TTX producers.